Personal remote assistance in Ambient Assisted Living: experimental research of elderly people’s trust and their intention to use - Steinke, Frederick; Ingenhoff, Alexander; Fritsch, Tobias (International journal of human computer interaction, 2014)
The objective of this article is to analyze the meaning of two different support functions regarding the use of Ambient Assisted Living (AAL). Thirty-two older persons (M age = 69.84, SD = 6.31) and a younger control group (n = 21; M age = 24.71, SD = 2.10) were examined in an experiment with three different tasks using a tablet computer. The first group operated with a mock-up that provided personal remote assistance (PRA) and the second group with one that provided embedded technical assistance (ETA). The main results show that older participants with PRA solve significantly more tasks than people with ETA. Moreover, a significant influence of perceived ease of use with PRA is revealed. Multiple regressions in the senior sample highlight a significant connection between trust in AAL technology and perceived reliability as well as perceived ease of use. No significant correlation between the type of assistance and older persons’ trust, as well as an intention to use AAL, was found.